An archaeology of abundance : re-evaluating the marginality of California's islands - Gill, Kristina, 1982-; Fauvelle, Mikael; Erlandson, Jon; Thompson, Victor D. (Society and ecology in island and coastal archaeology., 2019)
This volume focuses on the archaeology and historical ecology of a series of islands located off the Pacific Coast of Alta and Baja California, from the Channel Islands to Cedros Island.